Tool life in Turning Processes: Effect of Lubricants with a small amount of Graphite as Cutting Fluid - Agus Sutanto; Ismet Hari Mulyadi; Farchan - Vernando (Department of Mechanical Engineering, Universitas Andalas, 2022)
This study aims to determine the effect of various lubricant-based cutting fluid parameters to produce an optimal tool life in turning operations. This research does not use coolant as a cooling fluid, but as a lubricant with the addition of a small amount of graphite (solid lubricant) at a minimum quantity condition. By using HSS cutting tools and a low carbon steel workpiece, an experimental design was carried out using the Taguchi method with three parameters, that is the viscosity of the lubricant, the percentage of graphite in the lubricants, and the supplied pressure of the lubricants. Each parameter is designed to have three levels. The experimental results show that the percentage of graphite in the lubricant has the largest contribution of 52% and the viscosity of the lubricant is 38% while the fluid supplied pressure is only 7% of the tool life. Furthermore, based on the analysis of variance (ANOVA) it is known that the percentage of graphite and viscosity of the lubricant has a significant effect on the cutting tool life. The optimal and longest tool life is achieved when carried out with lubricant SAE20-50 with the percentage addition of 0.10% graphite with a pressure of 5 Bar.